Integration of Tiktok Videos and Students’ Performance in Hip-hop Dance Music - Generoso, Arnold B (Program Studi Pendidikan Seni Musik UPI, 2024)
This study determined the effect of the Tiktok Videos as a strategy in teaching Hip-hop Dance in Grade 10 MAPEH, specifically in teaching dance at Kapingkong National High School, Kapingkong, Lambayong, Sultan Kudarat, amidst the new normal setting. This study employed quasi-experimental and descriptive-evaluative research designs to determine and evaluate the effectiveness of the Tiktok Videos. It was carried out in Kapingkong National High School in Kapingkong, Lambayong, Sultan Kudarat, during the school year 2022-2023, amid a new normal setting. Based on the result, the creation of the Titktok videos, as to its style and organization, cultural sensitivity, creativity, content, music, language and captions, and instructional quality and comprehension follow the good standard in developing a video used as instructional materials in teaching as this rated as excellent by the evaluators.It has been concluded that there is no significant difference in the control and experimental groups' pretest scores in both cognitive and physical performance. Also, the Experimental group performed well in the posttest compared to the control group in cognitive and physical performance with the integration of Tiktok videos. There was a significant difference between the mean gain scores of the students under the control and experimental group. This significant difference was attributed to the use of Tiktok videos by the experimental group.